Peran Insecure Attachment terhadap Kekerasan Psikologis dalam Pacaran pada Perempuan Remaja Akhir - Arlin Aulia Andayu; Charyna Ayu Rizkyanti; Sri Juwita Kusumawardhani (Fakultas Psikologi, Universitas Islam Negeri (UIN) Sunan Gunung Djati Bandung, 2019)
The issues of dating violence take public attention recently. Psychological dating violence is one type of violence that has a serious impact on victims where women are more likely to experience it. Attachment theory is one of the risk factor that contributed in dating violence. The aim of this study is to determine whether insecure attachment (preoccupied, dismissive, and fearful avoidant) influence female to become victims of psychological dating violence. The sample of this research consists of 393 female late adolescents in Jakarta. Multiple Regression Analysis shows that insecure attachment impact significantly to the vurnerability of becoming victim in psychological dating violence among female late adolescents.